Criminality and crime: a social-cognitive-developmental theory of delinquent and criminal behavior - Walters, Glenn D. (Lexington Books, 2022)
"Criminality and Crime integrates criminality and participation in a specific criminal event. Although criminality and crime are normally considered separate entities, this book treats them as part of the same process, connected by their common association with criminal thinking"--